2005
DOI: 10.1002/ajh.20234
|View full text |Cite
|
Sign up to set email alerts
|

Small FVIII gene rearrangements in 18 hemophilia A patients: Five novel mutations

Abstract: Hemophilia A (HA) is a disorder caused by mutations of the FVIII gene, which is located on the tip of the long arm of the X chromosome. In a cohort of 18 unrelated Italian patients affected with HA of varying severity, we performed mutational screening of the gene by denaturing high-performance liquid chromatography (DHPLC) and direct sequencing of abnormal peaks. We identified five novel mutations and 9 previously reported DNA alterations. Two of the 9 previously reported alterations were each common to 3 unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Another case (ID 61) with the same mutation was found to be CRM negative. This change in CpG region has been reported several times in the HAMSTeRS database as occurring in mild/moderate HA patients and was also identified in other Indian studies [5], [24], suggesting that this change predominantly does not cause severe clinical manifestation in HA patients. Another case with mild deficiency of FVIII had p.Tyr737Cys (p.Tyr718Cys) mutation (ID 71) and was found to be CRM red , but not reported earlier in database.…”
Section: Discussionsupporting
confidence: 79%
“…Another case (ID 61) with the same mutation was found to be CRM negative. This change in CpG region has been reported several times in the HAMSTeRS database as occurring in mild/moderate HA patients and was also identified in other Indian studies [5], [24], suggesting that this change predominantly does not cause severe clinical manifestation in HA patients. Another case with mild deficiency of FVIII had p.Tyr737Cys (p.Tyr718Cys) mutation (ID 71) and was found to be CRM red , but not reported earlier in database.…”
Section: Discussionsupporting
confidence: 79%
“…The missense mutation detected in 2 independent families in our study in exon 16 of codon 1781 has been previously reported in the FVIII mutation database and has been detected in cases with mild and moderate phenotypes. [28][29][30] The amino acid change of arginine 1781 to histidine in exon 16 has been found in 3 patients with moderate phenotype. 31 Computational analysis has suggested that the amino acid substitution may produce a change in the tertiary structure of the FVIII polypeptide through a loss of salt bridge with D1846.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Sir, We recently described (1) anovel intron (IVS)19+4A/G substitution in apatient with severe haemophilia A(HA). HA (F8C; MIM#306700),the most common X-linked bleeding disorder, is caused by mutations throughoutthe FVIII gene ( FVIII) (2).…”
mentioning
confidence: 99%